The Use Of Scrabble Game As A Teaching Medium To Improve Students’ Vocabulary Mastery - Supriadi Supriadi; Jalaluddin Jalaluddin (JUPEIS : Jurnal Pendidikan dan Ilmu Sosial, 2023)
This study aims to examine the use of Scrabble game as a teaching medium to improve the vocabulary mastery of 2nd grade students of a Junior High School in West Nusa Tenggara Province, Indonesia. This research employed classroom action research (CAR). The subjects in this study were 27 2nd grade students. The data collection methods used in this research are observation, documentation, and tests. The results showed that the scrabble game medium was able to improve the vocabulary mastery of the students. This is evidenced by the increase in students' English vocabulary mastery in each cycle. In the first cycle the average value obtained was 62.37 (enough) out of 100 (very good) with a completeness percentage of 33% (unfinished) from 100% (completed) while in the second cycle the average value obtained by students increased from 62.37 (enough) to 77.37 (good) from 100 (very good) with the percentage of completeness reaching 70% (completed) from 100% (completed).